Going offline: broadening crowdfunding research beyond the online context. Issue 3 (3rd July 2017) - Gras, David; Nason, Robert S.; Lerman, Michael; Stellini, Meg
Abstract: Crowdfunding is often touted as a recent innovation that unleashes entrepreneurial potential by connecting entrepreneurs to small amounts of money from a broad base of individuals. However, literature on the topic has largely neglected the rich history of crowdfunding and failed to make an interesting and salient distinction between online and offline crowdfunding. This paper explicates the historical roots and current practices of offline crowdfunding, compares and contrasts online and offline crowdfunding, develops theoretically grounded predictions linking each type of crowdfunding to entrepreneurship outcomes, and offers related future research opportunities. We hope to build a rich appreciation for offline crowdfunding, provide insight into how crowdfunding as a financing mechanism has evolved and persists in contemporary society, and lay a foundation for future scholarly work in the area.